Re-anchoring the late Pleistocene tephrochronology of New Zealand based on concordant radiocarbon ages and combined 238U/230Th disequilibrium and (U–Th) /He zircon ages - Danisik, M.; Shane, P.; Schmitt, A.; Hogg, A.; Santos, G.; Storm, S.; Evans, Noreen; Fiffield, L.; Lindsay, J. (Elsevier Science BV, 2012)
The caldera-forming Rotoiti eruption from Okataina volcano was one of the largest rhyolite events of the last 100 ka in the Taupo Volcanic Zone, New Zealand. Its associated widespread tephra layer (Rotoehu tephra) is a significant time marker in terrestrial–marine paleoclimate correlation studies in the SW Pacific. However, the accurate and precise age of this eruption, and of the subsequent, smaller volume Earthquake Flat (EQF) eruption, has been the subject of controversy despite numerous studies. We have applied combined 238U/230Th disequilibrium and (U–Th)/He dating of zircon from Rotoiti and EQF deposits, and obtained overlapping ages of 45.1(7) ± 3.3 ka and 45.1(6) ± 2.9 ka, respectively. These results are supported by new and published high-precision radiocarbon data bracketing the age of the Rotoiti eruption between 44.8 ± 0.3 and 47.5 ± 2.1 ka cal BP. These age data are also in good agreement with a range of previously published estimates based on paleoclimate (palynology), luminescence dating of enclosing sediment, and sedimentation rates in terrestrial and marine settings. However, these results are at variance with a commonly quoted age of 60 ka, largely constrained by a single 40Ar/39Ar age of an overlying glassy lava flow at a distal tephra site. This study demonstrates the potential for combined 238U/230Th disequilibrium and (U–Th)/He dating of zircon in tephra and other volcanic deposits to provide age control in the 40–100 ka time interval, a period difficult to constrain using more traditional radiocarbon, K/Ar and 40Ar/39Ar methods.